Scintillator, scintillation screen, preparation method of scintillation screen and detector
By connecting the lithium compound ligand containing 6Li on the surface of the quantum dot, an efficient thermal neutron scintillator is solved, and the problems of low light yield and limited large-area applications in the prior art are achieved, and efficient photo yield and thermal neutron detection efficiency are achieved.
Patent Information
- Application Number
- CN202311164351.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
AI Technical Summary
The light yield of existing thermal neutron scintillators is low, and large-area applications are limited by preparation processes and costs.
The scintillator composed of quantum dots and ligands containing 6Li-containing lithium compound connected to the surface of the quantum dots improves the light yield through quantum effects and enhances the thermal neutron detection ability through lithium compounds containing 6Li.
Scintiles with high light yield and high thermal neutron detection efficiency have been achieved, reducing the preparation cost and are suitable for large-area applications.
Smart Images

Figure CN119592323A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of scintillation materials, and in particular to a scintillator, a scintillator screen, a preparation method thereof, and a detector. Background Art
[0002] Traditional thermal neutron scintillators mainly use enriched 6 Li isotope doping or dispersion in conventional scintillators, through 6 Li interacts with thermal neutrons to produce high-energy α particles, which collide with the scintillator and transfer energy to the scintillator, causing it to flash and emit light.
[0003] The most common thermal neutron scintillators are: 6 LiF doped ZnS(Ag) powder and Ce doped 6 Li silicate glass. 6 The scintillation light yield of LiF-doped ZnS(Ag) powder is low, while Ce-doped 6 Li silicate glass has low light yield and is only suitable for small area applications. 6 Li silicate glass is limited by its difficult process and high cost.
[0004] Therefore, it is urgent to find a thermal neutron scintillator with higher scintillation light yield. Summary of the invention
[0005] In view of this, the present application provides a scintillator, aiming to improve the problem of low light yield of existing scintillators.
[0006] The embodiment of the present application is implemented as follows: a scintillator includes a quantum dot and a nanostructured ... 6 Li is a lithium compound ligand.
[0007] Optionally, in some embodiments of the present application, the 6 Lithium compounds include 6 Inorganic lithium salts and lithium-containing 6 One or more organic lithium salts of Li.
[0008] Optionally, in some embodiments of the present application, the 6 Inorganic lithium salts of Li include 6 Lithium nitrate containing Li 6 Lithium carbonate, containing 6 Lithium sulfate, containing 6 Lithium hexafluorophosphate containing Li 6 Lithium chloride, containing 6 Lithium bromide, containing 6 Lithium iodide, containing 6One or more of lithium fluoride of Li; and / or
[0009] The said 6 Li organic lithium salts include 6 Lithium formate, containing 6 Lithium acetate, containing 6 Lithium oxalate, containing 6 Lithium acetonate, containing 6 Lithium butanone, containing 6 One or more of lithium trifluoromethanesulfonate of Li.
[0010] Optionally, in some embodiments of the present application,
[0011] The said 6 Lithium compounds 6 Li accounts for more than 98% of the total molar amount of lithium elements; and / or
[0012] The average particle size of the quantum dots is 3 to 10 nm; and / or
[0013] In the scintillator, the 6 The molar ratio of the lithium compound of Li to the quantum dots is 1:
[0014] (100~500).
[0015] Optionally, in some embodiments of the present application, the quantum dots include one or more of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, wherein:
[0016] The material of the quantum dots of the single structure, the core material of the quantum dots of the core-shell structure and the shell material of the quantum dots of the core-shell structure respectively include one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, and the II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, One or more of HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, S One or more of nSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound comprises GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, A One or more of lPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2;
[0017] The perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor, or an organic-inorganic hybrid perovskite semiconductor. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of the organic-inorganic hybrid perovskite semiconductor has a general structural formula of BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ 、Core-shell Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2 + , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of .
[0018] Optionally, in some embodiments of the present application, the quantum dots of the single structure include one or more of group II-VI quantum dots and group III-V quantum dots, the group II-VI quantum dots include one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, CdZnSeS, CdZnSeTe and CdZnSTe, and the group III-V quantum dots include one or more of InN, InP, InAs and InSb; and / or
[0019] The shell material of the core-shell structured quantum dots includes one or more of CdS, ZnS, and ZnCdS; and / or
[0020] The thickness of the shell layer of the quantum dots of the core-shell structure is less than or equal to 3 nm.
[0021] Optionally, in some embodiments of the present application, the quantum dots are further doped with doping elements, and the doping elements include one or more of Ag, Mn and Cu.
[0022] Optionally, in some embodiments of the present application, the molar ratio of the doping element to the quantum dots is 1:(10-80).
[0023] Correspondingly, an embodiment of the present application also provides a scintillator screen, comprising the above-mentioned scintillator.
[0024] Optionally, in some embodiments of the present application, the thickness of the scintillation screen is 0.1-1 mm.
[0025] Accordingly, the embodiment of the present application further provides a method for preparing a scintillation screen, comprising:
[0026] Providing quantum dots, and disposing the quantum dots on a substrate to obtain a quantum dot film;
[0027] Provide 6 Li lithium compound and solvent, mixed to obtain 6 Li compound solution containing 6 A lithium compound solution containing Li is disposed on at least one surface of the quantum dot film. 6 The lithium compound of Li undergoes ligand exchange with the quantum dots in the quantum dot film to form a scintillator, thereby obtaining a scintillator screen.
[0028] Optionally, in some embodiments of the present application, the thickness of the quantum dot film is in the range of 0.1 to 1 mm; and / or
[0029] The said 6 Lithium compound solution containing 6 The molar concentration of the lithium compound of Li is 0.1 to 2 mol / L; and / or
[0030] The said 6 Lithium compounds 6 Li accounts for more than 98% of the total molar amount of lithium elements; and / or
[0031] The said 6 The molar ratio of the lithium compound of Li to the quantum dots is in the range of 1:(100-500).
[0032] Optionally, in some embodiments of the present application, the solvent includes one or more of ethanol, isopropanol, propanol, and n-butanol.
[0033] Correspondingly, an embodiment of the present application also provides a detector, including the above-mentioned scintillation screen.
[0034] The scintillator described in the present application includes quantum dots and a 6 The quantum effect of quantum dots can effectively improve the light yield of the scintillator, and contains 6 The lithium compound ligand of Li can greatly improve the detection ability of quantum dots to thermal neutrons. In this way, the scintillator described in the present application can have both high light yield and high thermal neutron detection efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0036] Figure 1 It is a schematic structural diagram of a thermal neutron scintillation screen provided in an embodiment of the present application;
[0037] Figure 2 This is a flow chart of a method for preparing a thermal neutron scintillation screen provided in an embodiment of the present application;
[0038] Figure 3 is a TEM image of the quantum dot film of Example 1 of the present application;
[0039] Figure 4 This is a TEM image of the thermal neutron scintillation screen of Example 1 of the present application.
[0040] Reference numerals:
[0041] Thermal neutron scintillation screen 100 ; substrate 101 . DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0043] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0044] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0045] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0046] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0047] Due to the quantum effect, quantum dots generally have higher luminescence efficiency than bulk materials. For example, under the same conditions, Ag-doped ZnS quantum dots can obtain a higher scintillation light yield than ZnS (Ag) powder. In addition, quantum dots can be obtained using a solution method with low preparation cost, and can be processed onto large-area traditional glass substrates or flexible substrates by spraying, printing, and roller printing. Furthermore, quantum dot scintillators have the characteristics of high scintillation luminescence efficiency, low preparation cost, and suitability for large-area deposition processing, which can meet the market needs of large-area thermal neutron scintillators. However, the ligands of traditional quantum dots are mainly organic ligands, which cannot react with thermal neutrons to produce high-energy alpha particles to cause scintillator luminescence.
[0048] The technical solution of this application is as follows:
[0049] In a first aspect, an embodiment of the present application provides a thermal neutron scintillator, comprising a quantum dot and a ligand connected to the surface of the quantum dot, wherein the ligand comprises 6 In other words, the thermal neutron scintillator includes quantum dots and a 6 Li is a lithium compound ligand.
[0050] The said 6 The lithium compound of Li is a soluble substance that can be dissolved in water and / or organic solvents. 6 In some embodiments, the compound containing 6 The lithium compound of Li may include but is not limited to 6 Li inorganic lithium salts and 6 One or more organic lithium salts of Li.
[0051] In some embodiments, the 6 The inorganic lithium salt of Li may include but is not limited to 6 Lithium nitrate containing Li 6 Lithium carbonate, containing 6 Lithium sulfate, containing 6 Lithium hexafluorophosphate containing Li 6 Lithium chloride, containing 6 Lithium bromide, containing 6 Lithium iodide, containing 6 One or more of Li and lithium fluoride.
[0052] In some embodiments, the 6 The organic lithium salt of Li may include but is not limited to 6 Lithium formate, containing 6 Lithium acetate, containing 6 Lithium oxalate, containing 6 Lithium acetonate, containing 6 Lithium butanone, containing 6 One or more of lithium trifluoromethanesulfonate of Li.
[0053] The said 6 The anions in the lithium compound of Li can coordinate with the metal cations exposed on the surface of the quantum dots, and the 6 Lithium compounds 6 Li + The adsorption connection between the anion and the anion can be maintained through electrostatic attraction between the anion and the anion.
[0054] The thermal neutron scintillator described in the present application includes quantum dots and a 6 Lithium compound ligand, wherein the quantum effect of quantum dots can effectively improve the light yield of thermal neutron scintillator, and contains 6 The lithium compound ligand of Li can greatly improve the detection ability of quantum dots to thermal neutrons, so that the thermal neutron scintillator described in the present application can have both high light yield and high thermal neutron detection efficiency.
[0055] Furthermore, the existing thermal neutron scintillator with high light yield and high thermal neutron detection efficiency contains 6 When preparing Ag-doped ZnS powder of LiCl, 6 LiCl and Ag doped ZnS powders are heated to a molten state (temperature of about 800°C) for addition reaction, while the maximum temperature during the preparation of the thermal neutron scintillator described in the present application is about 220°C, and the present application contains 6 The addition of lithium compounds does not add too many complicated steps to the preparation of quantum dots. Therefore, the preparation cost of the thermal neutron scintillator described in the present application is low, suitable for the preparation of large-area thermal neutron scintillator screens, and more competitive in the market.
[0056] Furthermore, the 6 Lithium compound ligands can also effectively passivate defects on the surface of quantum dots, thereby further improving the light yield and thermal neutron detection efficiency of the thermal neutron scintillator.
[0057] In addition, the scintillation body of the thermal neutron scintillator described in the present application is quantum dots. Thus, when a thermal neutron scintillator described in the present application is used to prepare a thermal neutron scintillator screen, a flexible substrate can be used, and the prepared thermal neutron scintillator screen has a higher light yield and a higher thermal neutron detection efficiency. Thus, it can be used in special thermal neutron detection scenarios with irregular shapes (such as neutron detection in special-shaped stainless steel reactors, etc.) or in wearable thermal neutron detectors.
[0058] In at least one embodiment, the 6 The lithium compound of Li is 6 Li-enriched lithium compound. It can be understood that the 6 Lithium compounds may have isotopes 7 In some embodiments, the 6 Lithium compounds 6 Li accounts for more than 98% of the total molar amount of lithium elements. 6 Lithium compounds 6 The molar ratio of Li to total lithium is (0.98-1):1. In this way, the prepared thermal neutron scintillator can contain a higher content of6 Li, thereby making the thermal neutron scintillator have a higher light yield and a higher thermal neutron detection efficiency.
[0059] The quantum dots include one or more of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials (ie, perovskite quantum dots).
[0060] It can be understood that the quantum dots with a single structure refer to quantum dots that do not include a shell layer.
[0061] In some implementations, the material of the quantum dots of the single structure, the core material of the quantum dots of the core-shell structure, and the shell material of the quantum dots of the core-shell structure, respectively, include but are not limited to one or more of II-VI compounds, IV-VI compounds, III-V compounds, and I-III-VI compounds, wherein the II-VI compounds include but are not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, One or more of HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compounds include but are not limited to SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnS One or more of SnS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compounds include but are not limited to GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs , AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compounds include but are not limited to one or more of CuInS2, CuInSe2 and AgInS2.
[0062] Furthermore, in some embodiments, the quantum dots of the single structure include one or both of metal elements and non-metal elements. The metal elements include but are not limited to one or more of Zn, Cd and In, and the non-metal elements include but are not limited to one or more of S, Se, Te, N, P and As.
[0063] As an example, the quantum dots of the single structure include but are not limited to one or more of the quantum dots of the II-VI group and the quantum dots of the III-V group. The quantum dots of the II-VI group include but are not limited to one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, CdZnSeS, CdZnSeTe and CdZnSTe, and the quantum dots of the III-V group include but are not limited to one or more of InN, InP, InAs and InSb.
[0064] Furthermore, in some embodiments, the shell material of the core-shell structured quantum dots includes but is not limited to one or more of CdS, ZnS, and ZnCdS.
[0065] The shell thickness of the core-shell structured quantum dots is less than or equal to 3 nm, for example, 0.5 nm, 0.8 nm, 1 nm, 1.2 nm, 1.5 nm, 1.6 nm, 1.8 nm, 2 nm, 2.2 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.8 nm, 3 nm, etc. Within the shell thickness range, it is beneficial to 6 The α particles generated by Li act on the quantum dot core, thereby maximizing the energy of the α particles and transferring them to the quantum dot core, thereby making the thermal neutron scintillator including the quantum dots of the core-shell structure have a higher light yield and a higher thermal neutron detection efficiency.
[0066] The perovskite semiconductor material may include but is not limited to doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3]2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of .
[0067] In some embodiments, the average particle size of the quantum dots is 3-10 nm. Within the range, the quantum dots have higher stability and light yield, which is beneficial for the thermal neutron scintillator to have higher light yield and higher thermal neutron detection efficiency.
[0068] In some embodiments, in the thermal neutron scintillator, the 6 The molar ratio of the lithium compound ligand of Li to the quantum dots is 1:(100-500), for example, 1:(100-300), 1:(120-320), 1:(150-350), 1:(180-380), 1:(200-400), 1:(220-420), 1:(250-450), 1:(280-480), 1:(300-500), etc., and for example, 1:100, 1:120, 1:150, 1:180, 1:200, 1:220, 1:250, 1:280, 1:300, 1:320, 1:350, 1:380, 1:400, 1:420, 1:450, 1:480, 1:500, etc. Within the molar ratio range, the surface of the quantum dots can be connected with an appropriate amount of 6 The lithium compound ligand of Li makes the thermal neutron scintillator have higher film quality, higher light yield and higher thermal neutron detection efficiency.
[0069] In some embodiments, the quantum dots are further doped with doping elements, and the doping elements include but are not limited to one or more of Ag, Mn and Cu. In at least one embodiment, the quantum dots are Ag-doped ZnS quantum dots. It can be understood that when the quantum dots are quantum dots of a core-shell structure, the doping elements can be doped only in the shell, or only in the core, or entangled in the shell and the core at the same time. In at least one embodiment, the doping elements are doped in the core of the quantum dots of the core-shell structure.
[0070] In some embodiments, when the quantum dots contain doping elements, the molar ratio of the doping elements to the quantum dots in the quantum dots is 1:(10-80), for example, 1:(10-50), 1:(15-55), 1:(20-60), 1:(25-65), 1:(30-70), 35-75), 1:(40-78), 1:(45-80), etc., and for example, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55, 1:60, 1:65, 1:70, 1:75, 1:80, etc. Within the ratio range, the quantum dots can have higher stability and light yield, which is beneficial for the thermal neutron scintillator to have higher light yield and higher thermal neutron detection efficiency.
[0071] Second, see Figure 1 The embodiment of the present application further provides a thermal neutron scintillator screen 100 , wherein the thermal neutron scintillator screen 100 includes the thermal neutron scintillator described above.
[0072] In some embodiments, the thermal neutron scintillation screen 100 has a thickness of 0.1-1 mm. Within the thickness range, the thermal neutron scintillation screen 100 has a high thermal neutron absorption capability.
[0073] In some embodiments, at least one surface of the thermal neutron scintillation screen 100 is combined with a substrate 101. The substrate 101 can be a rigid substrate or a flexible substrate, wherein the rigid substrate includes but is not limited to a glass substrate, a metal substrate or a ceramic substrate, and the flexible substrate includes but is not limited to a polymer substrate.
[0074] The material of the ceramic substrate includes, but is not limited to, one or more of alumina, silicon nitride, silicon carbide, zirconium dioxide, aluminum nitride, magnesium aluminum spinel, and yttrium aluminum garnet.
[0075] The material of the polymer substrate includes, but is not limited to, one or more of polyethylene terephthalate, polyimide, polystyrene or polycarbonate.
[0076] The thermal neutron scintillator screen 100 described in the present application includes the thermal neutron scintillator described above, and has a higher light yield and a higher thermal neutron detection efficiency.
[0077] In addition, for the same thickness and the same content 6 The thermal neutron scintillator 100 prepared by the thermal neutron scintillator described in the present application has a higher light yield and detection efficiency than the existing thermal neutron scintillator containing lithium compounds. 6Thermal neutron scintillator screen prepared by Ag-doped ZnS powder of LiCl (Ag-doped ZnS powder scintillator screen).
[0078] Third, see Figures 1-2 The present application also provides a method for preparing the thermal neutron scintillation screen, comprising the following steps:
[0079] Step S11, providing quantum dots, wherein the surface of the quantum dots is connected with organic ligands, and the quantum dots are disposed on a substrate 101 to obtain a quantum dot film;
[0080] Step S12: providing 6 Li lithium compound and solvent, mixed to obtain 6 Li compound solution containing 6 A lithium compound solution containing Li is disposed on at least one surface of the quantum dot film. 6 The lithium compound of Li undergoes ligand exchange with the quantum dots in the quantum dot film to form a thermal neutron scintillator, thereby obtaining the thermal neutron scintillator screen 100 .
[0081] It is understandable that the organic ligand is an organic ligand known to be connected to the surface of the quantum dot. As an example, the organic ligand includes but is not limited to one or more of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine and polyvinyl pyridine. The acid ligand includes but is not limited to one or more of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid and stearic acid, the thiol ligand includes but is not limited to one or more of octadecyl mercaptan, dodecyl mercaptan and octadecyl mercaptan, the amine ligand includes but is not limited to one or more of oleylamine, octadecylamine and octadecylamine, and the (oxygen) phosphine ligand includes but is not limited to one or more of trioctylphosphine and trioctylphosphine oxide.
[0082] The method for preparing the thermal neutron scintillation screen described in the present application comprises first forming a quantum dot film, and then arranging a 6 Lithium compound solution, 6 The lithium compound of Li undergoes ligand exchange with the quantum dots in the quantum dot film to form a thermal neutron scintillator, and then obtains the thermal neutron scintillator screen 100. In this way, the problem of directly mixing the thermal neutron scintillator solution with the containing 6 When the lithium compound solution of Li is mixed, 6 The chain length of Li lithium compounds is relatively short, and the spontaneous aggregation of quantum dots cannot be overcome in the solution system, resulting in the problem that the quantum dots are easily precipitated and cannot be redispersed in the solvent or have poor dispersibility.
[0083] In the step S11:
[0084] The quantum dots are described above and will not be described again here.
[0085] The method for preparing the quantum dots is a known method for preparing quantum dots. Taking quantum dots of a single structure as an example, in at least one embodiment, the method for preparing the quantum dots comprises: providing a cation source, an anion source and an organic solvent, mixing, and crystallizing to obtain quantum dots.
[0086] In some embodiments, the cation source includes, but is not limited to, one or more of a zinc source, a cadmium source, and an indium source.
[0087] In some embodiments, the zinc source includes but is not limited to one or more of dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc oleate, zinc stearate, zinc undecylenate, zinc hydroxide and zinc peroxide.
[0088] In some embodiments, the cadmium source includes but is not limited to one or more of cadmium oleate, cadmium butyrate, cadmium hexanate, cadmium hexanoate, cadmium octanoate, cadmium dodecanoate, cadmium myristate, cadmium palmitate, and cadmium stearate.
[0089] In some embodiments, the indium source includes, but is not limited to, one or more of indium chloride, indium bromide, indium iodide, indium acetate, indium carbonate, indium nitrate, indium perchlorate, and indium cyanide.
[0090] In some embodiments, the anion source includes, but is not limited to, one or more of a sulfur source, a selenium source, a tellurium source, a nitrogen source, a phosphorus source, and an arsenic source.
[0091] In some embodiments, the sulfur source includes but is not limited to one or more of sulfur powder, trioctylphosphine sulfur, tributylphosphine sulfur, sulfur-octadecene solution, sulfur-oleylamine solution and a thiol compound with a chemical formula of R-SH, wherein R is one or more of an alkyl group with a carbon number ≥ 6.
[0092] In some embodiments, the selenium source includes, but is not limited to, one or more of trioctylphosphine selenium, tributylphosphine selenium, selenium-octadecene solution, selenium-oleylamine solution, and selenide diphenylphosphine compounds.
[0093] In some embodiments, the tellurium source includes, but is not limited to, one or more of trioctylphosphine tellurium, tributylphosphine tellurium, tellurium-octadecene solution, and diphenylditellurium compound.
[0094] In some embodiments, the nitrogen source includes, but is not limited to, one or more of oleylamine, dipropylamine, n-hexylamine, n-octylamine, trioctylamine, octaamine, dodecylamine, octadecylamine, hexadecylamine, and tetradecylamine.
[0095] In some embodiments, the phosphorus source includes, but is not limited to, one or more of tris(dimethylamino)phosphine, tris(diethylamino)phosphine, and tris(trimethylsilyl)phosphine.
[0096] In some embodiments, the arsenic source includes, but is not limited to, one or more of arsine and tris(trimethylsilyl)-arsine.
[0097] In some embodiments, the organic solvent includes, but is not limited to, one or more of n-dodecyl mercaptan and oleylamine.
[0098] When the quantum dots further include a doping element, the preparation method further includes a step of adding a compound containing the doping element into the system before the thermal reaction.
[0099] The compound containing the doping element includes, but is not limited to, one or more of a silver compound, a manganese compound, and a copper compound.
[0100] In some embodiments, the silver compound includes, but is not limited to, one or more of silver nitrate, silver acetate, and silver oxide.
[0101] In some embodiments, the manganese compound includes, but is not limited to, one or more of manganese nitrate, manganese acetate, manganese sulfate, manganese chloride, manganese bromide, and manganese oxide.
[0102] In some embodiments, the copper compound includes, but is not limited to, one or more of copper nitrate, copper acetate, copper sulfate, copper chloride, copper bromide, and copper oxide.
[0103] The substrate 101 is as described above and will not be described again herein.
[0104] In some embodiments, the thickness of the quantum dot film ranges from 0.1 to 1 mm, for example, 0.1 to 0.6 mm, 0.2 to 0.7 mm, 0.3 to 0.8 mm, 0.4 to 0.9 mm, 0.5 to 1.0 mm, etc., and for example, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, etc. Within the thickness range, it is beneficial to prepare a thermal neutron scintillator screen with good thermal neutron absorption capability.
[0105] The method of setting the quantum dots on the substrate 101 can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical coating and solution method, among which the physical coating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion coating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip-pull method, immersion method, spray coating, roll coating, casting, slit coating, and strip coating, etc.
[0106] In the step S12:
[0107] The said 6 Lithium compound solution containing 6 The molar concentration of the lithium compound of Li is 0.1-2 mol / L, for example, 0.1-1 mol / L, 0.5-1.5 mol / L, 0.8-1.8 mol / L, 1.2-2 mol / L, etc., and for example, 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, etc. Within the concentration range, it is beneficial to 6 The lithium compounds of Li and quantum dots can effectively and fully exchange ligands, which is beneficial to the preparation of a thermal neutron scintillation screen with a higher surface flatness, and further beneficial to the preparation of a thermal neutron scintillation screen with a higher light yield and higher thermal neutron detection efficiency.
[0108] The solvent is not limited to one or more of ethanol, isopropanol, propanol, and n-butanol. 6 The lithium compound of Li can have good wettability to quantum dots and will not dissolve the quantum dots. 6 The lithium compound of Li and the quantum dots exchange ligands to provide the required liquid environment. In addition, the boiling point of the solvent is low and it is easy to remove.
[0109] It is understandable that the 6 Lithium compounds may have isotopes 7 In some embodiments, the 6 Lithium compounds 6 Li accounts for more than 98% of the total molar amount of lithium elements.6 Lithium compounds 6 The molar ratio of Li to total lithium is (0.98-1):1. In this way, the prepared thermal neutron scintillator can contain a higher content of 6 Li, thereby making the thermal neutron scintillator have a higher light yield and a higher thermal neutron detection efficiency.
[0110] The said 6 The molar ratio of the lithium compound of Li to the quantum dots is in the range of 1:(100-500), for example, 1:(100-300), 1:(120-320), 1:(150-350), 1:(180-380), 1:(200-400), 1:(220-420), 1:(250-450), 1:(280-480), 1:(300-500), etc., and for example, 1:100, 1:120, 1:150, 1:180, 1:200, 1:220, 1:250, 1:280, 1:300, 1:320, 1:350, 1:380, 1:400, 1:420, 1:450, 1:480, 1:500, etc. Within the molar ratio range, the surface of the quantum dots can be connected with an appropriate amount of 6 The lithium compound ligand of Li is beneficial to prepare a thermal neutron scintillation screen with higher film quality, higher light yield and higher thermal neutron detection efficiency.
[0111] The surface of the quantum dot film is provided with 6 The method for preparing a lithium compound solution containing Li may be the solution method described above. In at least one embodiment, the method for arranging the quantum dots on the substrate comprises: 6 A lithium compound solution of Li is sprayed on the surface of the quantum dot film.
[0112] In some embodiments, the step S13 further includes a step of packaging the thermal neutron scintillator screen, so that the thermal neutron scintillator in the thermal neutron scintillator screen can be effectively prevented from being affected by external moisture.
[0113] In a fourth aspect, an embodiment of the present application further provides a thermal neutron detector, comprising the thermal neutron scintillation screen 100 described above.
[0114] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0115] Example 1
[0116] Synthesis of Ag-doped ZnS quantum dots:
[0117] 43.9g zinc acetate dihydrate, 51.3g sulfur powder and 1.69g silver nitrate were added to a three-necked flask with a volume of 2L, and then 400mL of n-dodecyl mercaptan and 600mL of oleylamine with a purity of 70% were added to the three-necked flask. The flask was switched to a nitrogen atmosphere by evacuating and filling with nitrogen for 3 cycles, and then the flask was heated at 220°C and maintained for 0.5h to allow the reaction to proceed fully to obtain a reaction solution. After the reaction was completed, the flask was naturally cooled to room temperature, and the reaction solution was added to acetone to obtain 18g Ag-doped ZnS quantum dots. After centrifugation, the lower precipitate was collected and redispersed in toluene, and the precipitation-centrifugation-redispersion process was repeated 3 times to wash away impurities.
[0118] Quantum dot film preparation:
[0119] The toluene solution of Ag-doped ZnS quantum dots was processed onto the plastic film by spraying to obtain a quantum dot film with a thickness of 0.5 mm.
[0120] Thermal neutron scintillation screen preparation:
[0121] 0.0414g 6 Lithium chloride (M = 42.39, n = 0.96 mmol) 6 Li accounts for 98% of the total molar amount of lithium element) solution was dissolved in 2 mL of ethanol to obtain 6 Li-containing lithium chloride solution, 6 The lithium chloride solution of Li is evenly processed onto the quantum dot film by spraying, so that 6 LiCl exchanges ligands with quantum dots in the quantum dot film and is connected to the surface of the quantum dots to form a thermal neutron scintillator, thereby obtaining a thermal neutron scintillator screen.
[0122] Encapsulation to protect the thermal neutron scintillator screen from external moisture.
[0123] Example 2
[0124] This embodiment is substantially the same as Embodiment 1, except that the quantum dots in this embodiment are not doped with Ag, that is, the quantum dots in this embodiment are ZnS quantum dots.
[0125] Example 3
[0126] This embodiment is substantially the same as Embodiment 1, except that CdSe quantum dots are used in this embodiment to replace the Ag-doped ZnS quantum dots in Embodiment 1.
[0127] Example 4
[0128] This embodiment is substantially the same as Embodiment 1, except that InP quantum dots are used in this embodiment to replace the Ag-doped ZnS quantum dots in Embodiment 1.
[0129] Example 5
[0130] This embodiment is basically the same as Embodiment 1, except that the thickness of the quantum dot film in this embodiment is 0.1 mm.
[0131] Example 6
[0132] This embodiment is basically the same as Embodiment 1, except that the thickness of the quantum dot film in this embodiment is 1 mm.
[0133] Example 7
[0134] This embodiment is substantially the same as Embodiment 1, except that the amount of lithium chloride used in this embodiment is 0.0166 g.
[0135] Example 8
[0136] This embodiment is substantially the same as embodiment 1, except that the amount of lithium chloride used in this embodiment is 0.0828 g.
[0137] Example 9
[0138] This embodiment is substantially the same as embodiment 1, except that the amount of silver nitrate used in this embodiment is 0.676 g.
[0139] Example 10
[0140] This embodiment is substantially the same as embodiment 1, except that the amount of silver nitrate used in this embodiment is 3.38 g.
[0141] Embodiment 11
[0142] This embodiment is basically the same as embodiment 1, except that 6 The lithium fluoride of Li replaces the lithium fluoride in Example 1 6 Lithium chloride.
[0143] Example 12
[0144] This embodiment is substantially the same as Embodiment 1, except that 1.73 g of manganese acetate is used in this embodiment to replace 1.69 g of silver nitrate in Embodiment 1.
[0145] Embodiment 13
[0146] This embodiment is substantially the same as embodiment 1, except that 1.81 g of copper acetate is used in this embodiment to replace 1.69 g of silver nitrate in embodiment 1.
[0147] Embodiment 14
[0148] This embodiment is basically the same as embodiment 1, except that 6The lithium nitrate of Li replaces the lithium nitrate in Example 1 6 Lithium chloride.
[0149] Embodiment 15
[0150] This embodiment is basically the same as embodiment 1, except that 6 The lithium acetate of Li replaces the lithium acetate in Example 1 6 Lithium chloride.
[0151] Example 16
[0152] This embodiment is basically the same as the embodiment 1, except that the present embodiment uses CsPbBr3 perovskite quantum dots to replace the Ag-doped ZnS quantum dots in the embodiment 1. 6 The lithium bromide of Li replaces the lithium bromide in Example 1 6 Lithium chloride.
[0153] Embodiment 17
[0154] This embodiment is basically the same as Embodiment 1, except that this embodiment uses CdSe / ZnS core-shell structured quantum dots to replace the Ag-doped ZnS quantum dots in Embodiment 1, wherein the core CdSe of the CdSe / ZnS core-shell structured quantum dots is doped with Ag, and the thickness of the ZnS shell layer is 2 nm.
[0155] Comparative Example 1
[0156] The thermal neutron scintillator screen of this comparative example is a commercial 6 Li (Saint Gobain, BC-704) doped ZnS (Ag) powder thermal neutron scintillation screen, thickness 0.5mm.
[0157] Comparative Example 2
[0158] The thermal neutron scintillator screen of this comparative example is a commercial 6 Li silicate glass (Saint Gobain, GS1) thermal neutron scintillation screen, thickness 0.5 mm.
[0159] The quantum dot film of Example 1 (i.e. 6 LiCl ligand exchange membrane) and thermal neutron scintillation screen (i.e. 6 The membrane after LiCl ligand exchange was tested by TEM, and the results were Figure 3 and Figure 4 TEM image shown.
[0160] Depend on Figures 3-4 It can be seen that the distance between quantum dots after ligand exchange is smaller, which may be because the long-chain ligands on the surface of the quantum dots are replaced by short-chain ligands.
[0161] The thermal neutron scintillation screen of Example 1 was subjected to EDS detection. The detection results are shown in Table 1.
[0162] Table 1:
[0163] element Atomic mass percentage Zinc 49.0% sulfur 47.8 chlorine 0.5% silver 2.7%
[0164] It can be seen from Table 1 that the thermal neutron scintillator screen of Example 1 contains Ag and Cl elements, which proves that the quantum dots in the thermal neutron scintillator screen are doped with Ag and Cl is connected to the surface of the quantum dots.
[0165] The thermal neutron scintillation screens of Examples 1 to 17 and Comparative Examples 1 to 2 were tested for light yield and thermal neutron detection efficiency. The test results are shown in Table 2.
[0166] The test method of light yield is as follows: using Saint Gobain's BC-400 as a standard, using a thermal neutron source to excite the scintillator and integrating the measured luminescence signal S0 through a photomultiplier tube, using the same thermal neutron source to test the luminescence peak area S of other scintillators of the same mass, thereby obtaining the relative light yield of the scintillator to anthracene, S / S0*100%;
[0167] The test method for thermal neutron detection efficiency is: use a calibrated detector including the thermal neutron scintillator screens of Examples 1 to 12 and Comparative Examples 1 to 2 to test the neutron flux A of the thermal neutron source, in units of pieces / second / square centimeter, and then collect the luminescence of the scintillator for a certain time t through a photomultiplier tube and integrate it to obtain the number of emitted photons N, the luminescent area of the scintillator is S, and the detection efficiency is N / S / t / A*100%.
[0168] Table 2:
[0169]
[0170] From Table 2 we can see that:
[0171] Compared with the thermal neutron scintillator screens of comparative examples 1 to 2, the thermal neutron scintillator screens of embodiments 1 to 17 have higher light yield and higher thermal neutron detection efficiency, and have lower cost;
[0172] Compared with the thermal neutron scintillator of Example 1, the light yield and thermal neutron detection efficiency of the thermal neutron scintillator of Example 17 are lower. It can be seen that the thermal neutron scintillator containing quantum dots of a single structure has a higher light yield and thermal neutron efficiency. The reason may be that the high-energy α particles generated by 6Li in the thermal neutron scintillator have a relatively shallow action depth, and the shell layer of the core-shell structure hinders the energy transfer of high-energy α particles to the quantum dot core to a certain extent.
[0173] The thermal neutron scintillator, thermal neutron scintillator screen and preparation method thereof, and thermal neutron detector provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A scintillator, characterized in that: It includes quantum dots and ligands connected to the surface of the quantum dots, wherein the ligands include 6 Li is a lithium compound.
2. The scintillator according to claim 1, characterized in that The said 6 Lithium compounds include 6 Inorganic lithium salts and lithium-containing 6 One or more organic lithium salts of Li.
3. The scintillator according to claim 2, characterized in that: The said 6 Inorganic lithium salts of Li include 6 Lithium nitrate containing Li 6 Lithium carbonate, containing 6 Lithium sulfate, containing 6 Lithium hexafluorophosphate containing Li 6 Lithium chloride, containing 6 Lithium bromide, containing 6 Lithium iodide, containing 6 One or more of lithium fluoride of Li; and / or The said 6 Li organic lithium salts include 6 Lithium formate, containing 6 Lithium acetate, containing 6 Lithium oxalate, containing 6 Lithium acetonate, containing 6 Lithium butanone, containing 6 One or more of lithium trifluoromethanesulfonate of Li.
4. The scintillator according to claim 1, characterized in that: The said 6 Lithium compounds 6 Li accounts for more than 98% of the total molar amount of lithium elements; and / or In the scintillator, the 6 The molar ratio of the lithium compound of Li to the quantum dots is 1: (100-500); and / or The average particle size of the quantum dots is 3 to 10 nm.
5. The scintillator according to claim 1, characterized in that: The quantum dots include one or more of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, wherein: The material of the quantum dots of the single structure, the core material of the quantum dots of the core-shell structure and the shell material of the quantum dots of the core-shell structure respectively include one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, and the II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, One or more of HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, S One or more of nSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound comprises GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, A One or more of lPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; The perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor, or an organic-inorganic hybrid perovskite semiconductor. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of the organic-inorganic hybrid perovskite semiconductor has a general structural formula of BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of .
6. The scintillator according to claim 5, characterized in that: The single-structure quantum dots include one or more of group II-VI quantum dots and group III-V quantum dots, the group II-VI quantum dots include one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, CdZnSeS, CdZnSeTe and CdZnSTe, and the group III-V quantum dots include one or more of InN, InP, InAs and InSb; and / or The shell material of the core-shell structured quantum dots includes one or more of CdS, ZnS, and ZnCdS; and / or The thickness of the shell layer of the quantum dots of the core-shell structure is less than or equal to 3 nm.
7. The scintillator according to any one of claims 1 to 6, characterized in that: The quantum dots are further doped with doping elements, and the doping elements include one or more of Ag, Mn and Cu; Optionally, the molar ratio of the doping element to the quantum dots is 1:(10-80).
8. A flashing screen, characterized in that: A scintillator comprising the scintillator according to any one of claims 1 to 7.
9. The scintillation screen according to claim 8, characterized in that: The thickness of the scintillation screen is 0.1-1 mm.
10. A method for preparing a scintillating screen, characterized in that: include: Providing quantum dots, and disposing the quantum dots on a substrate to obtain a quantum dot film; Provide 6 Li lithium compound and solvent, mixed to obtain 6 Li compound solution containing 6 A lithium compound solution of Li is disposed on at least one surface of the quantum dot film to perform ligand exchange to form a scintillator and obtain a scintillator screen.
11. The preparation method according to claim 10, characterized in that: The thickness of the quantum dot film is 0.1 to 1 mm; and / or The said 6 Lithium compound solution containing 6 The molar concentration of the lithium compound of Li is 0.1 to 2 mol / L; and / or The said 6 Lithium compounds 6 Li accounts for more than 98% of the total molar amount of lithium elements; and / or The said 6 The molar ratio of the lithium compound of Li to the quantum dots is in the range of 1:(100-500); and / or The solvent includes one or more of ethanol, isopropanol, propanol, and n-butanol.
12. A detector, characterized in that: The invention comprises a scintillation screen as described in any one of claims 8 to 9, or a scintillation screen prepared by the preparation method as described in any one of claims 10 to 11.
Citation Information
Cited By
Boron nitride neutron scintillation screen with submicron resolution and boron-10 isotope enrichment
CN122307628A